From Top Down Under: New Insights into the Social Significance of Superimpositions in the Rock Art of Northern Kimberley, Australia. Issue 3 (August 2019) - Motta, Ana Paula
Abstract : Rock-art researchers have long acknowledged the importance of discerning superimposition sequences as a means for exploring chronology. Despite their potential for reconstructing painting events and thus informing on a site's production sequences, the social significance of superimpositions and their associated meanings have been little explored. In the Kimberley Region of northwestern Australia, interpretations of superimpositions as an analytical lens have often lingered on the 'negative' connotations of this practice (e.g. to destroy supernatural power embedded in previous paintings and/or to show cultural dominance). As a result, it has been proposed that the overpainting of previous images was tantamount to defacing, leading to the proposition that new images constituted a form of vandalism of older art. In this paper, a sample of rock-art sites from the northwestern and northeastern Kimberley is analysed with the aim of grounding the study of superimpositions in more nuanced practices, leading researchers to contemplate the role they played among populations within the same area. It is argued here that superimpositions brought together past and present experiences that served to reinforce the links between contemporary art production and the inherited landscape.